A Novel Approach for Amplification and Purification of Mouse Oligodendrocyte Progenitor Cells - Yang, Junlin; Cheng, Xuejun; Shen, Jiaxi; Xie, Binghua; Zhao, Xiaofeng; Zhang, Zunyi; Cao, Qilin; Shen, Ying; Qiu, Mengsheng (Frontiers in Cellular Neuroscience, 2016)
Although transgenic and knockout mice are widely used to study the specification and differentiation of oligodendrocyte precursor cells (OPCs), mouse primary OPCs are difficult to be purified and maintained, and many in vitro studies have to resort to rat OPCs as substitutes. In this study, we reported that mouse O4 negative early-stage OPCs can be obtained by culturing cortical tissue blocks, and the simultaneous treatment of OPCs with PDGFaa, bFGF and EGF is the key for the propagation of mouse OPCs in culture. Epidermal growth factor (EGF) was found to be a potent mitogen for OPCs and cooperate with Platelet Derived Growth Factor-AA (PDGFaa) to extend cell division and inhibit their differentiation. EGF also collaborates with PDGFaa and basic fibroblast growth factor (bFGF) to convert bipolar or tripolar OPCs to more vital fibroblast-like OPCs without compromising their oligodendrocyte differentiation potential. In addition, EGF promoted the survival and proliferation of glial progenitor cells (GPCs) derived from primary OPC cultures, and a mixture of GPCs and OPCs can be obtained and propagated in the presence of EGF, bFGF and PDGFaa. Once EGF is withdrawn, GPC population decreased sharply and fibroblast-like OPCs changed into typical OPCs morphology, then homogeneous OPCs were obtained subsequently.